At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Y=6x 2x+3y=-20. (Solving by substitution)

Sagot :

y=6x, 2x+3y=-20
Substitution means just plugging in another equation equal to a single variable in order to solve for the other variable, and then the first. In this case, the equation being plugged in is y=6x, so 6x will be put in place of y in the equation 2x+3y=-20.
2x+3(6x)=-20
2x+18x=-20
20x=-20
x=-1
And then x=-1 can be plugged into the original equation to find y. (And, if you wish, into the y= equation to check it.)
2(-1)+3y=-20
-2+3y=-20
3y=-20+2
3y=-18
y=-6
And to check it, we plug the two into the original y= equation.
y=6x
-6=6(-1)
-6=-6
They are equal, so both check out.
x=-1, y=-6
This is straight forward:

y = 6x      ...............(i)

2x + 3y = -20  ...........(ii)
 
  We simply substitute (i) into (ii)

2x +3(6x) = -20
2x + 18x = -20
20x = -20
x = -20/20
x = -1.

Recall  y = 6x
              y = 6(-1) = -6.
x = -1,  y = -6.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.